Analisis Komparatif Pada Puisi “Stopping By Woods On The Snow Evening” Oleh Robert Frost - Hafiza Saumi Ramadilla; Halimah Br Surbakti; Rahel Raphita Sinabutar; Elyana Feronica Manurung; Yolanda Marchella; Tri Indah Prasasti (Journal on Education, 2024)
The poem "Stopping by Woods on a Snowy Evening" by Robert Frost is one of the world's most famous works of literature. The translation of this poem into Indonesian presents its own challenges for the translator, especially in maintaining the style, atmosphere, and message desired by the poet. This study aims to analyze stylistic changes that occur in the translation of this poem from English to Indonesian. Using a comparative approach, this study compares stylistic elements such as diction, metaphor, rhyme, and rhythm between the original text and the translation. Robert Frost's poems received many prestigious international awards, including the Nobel Prize. The poem is characterized by its depth, its mysterious nature, and its profound meaning. As mentioned earlier, many critics have varying perspectives when analyzing this poem. Regardless of his interpretation, Frost effectively provides readers and literary enthusiasts with various literary components that can be analyzed in the text. The many literary elements contained in this poem make it interesting to listen to.